2022
DOI: 10.1021/acsomega.2c04778
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Derivatives of the Antifungal Peptoid RMG8-8

Abstract: Cryptococcal meningitis, caused by the fungal pathogen Cryptococcus neoformans, is a devastating disease with a mortality rate of over 80%. Due to the increasing prevalence of resistance to antifungals and the high mammalian toxicity of current treatments, the development of new antifungal therapies is vital. In an effort to improve the biological properties of a previously discovered antifungal peptoid, termed RMG8-8, an iterative structure–activity relationship study was conducted. This three-round study sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Peptoids are commonly purified using reverse-phase high-performance liquid chromatography (HPLC), which separates the crude mixture on the basis of polarity. Yields of 30–60% are commonly reported for pure fractions of peptoids obtained using reverse-phase HPLC. ,, The recycling GPC separates the crude mixture on the basis of size, yet adsorption to the packing material can occur as the peptoid is passed over it multiple times, potentially reducing the final yields. In our work, the yield of Npe 6 following purification by recycling GPC still fell within the range typically obtained using reverse-phase HPLC.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Peptoids are commonly purified using reverse-phase high-performance liquid chromatography (HPLC), which separates the crude mixture on the basis of polarity. Yields of 30–60% are commonly reported for pure fractions of peptoids obtained using reverse-phase HPLC. ,, The recycling GPC separates the crude mixture on the basis of size, yet adsorption to the packing material can occur as the peptoid is passed over it multiple times, potentially reducing the final yields. In our work, the yield of Npe 6 following purification by recycling GPC still fell within the range typically obtained using reverse-phase HPLC.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, several studies have shown that peptoids have low cytotoxicity [20–25] . Taking the advantages of these advantages, peptoids are applied to non‐fouling coatings, [6,26,27] protein‐purification components, [28–31] antibacterial agents, [32–39] and therapeutic agents [36,40–45] …”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Moreover, several studies have shown that peptoids have low cytotoxicity. [20][21][22][23][24][25] Taking the advantages of these advantages, peptoids are applied to non-fouling coatings, [6,26,27] protein-purification components, [28][29][30][31] antibacterial agents, [32][33][34][35][36][37][38][39] and therapeutic agents. [36,[40][41][42][43][44][45] Amphiphilic peptoids also have been investigated and various kinds of self-assemblies were created as same as peptides.…”
Section: Introductionmentioning
confidence: 99%